The Gut Brain Axis: An Evolving Paradigm in Health and Disease - Ajit Pahari; Sanjit Kumar Kar; Bishal Joshi (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION The gut-brain axis (GBA) is a communication network connecting the central and enteric nervous system, linking brain emotion and cognition with intestinal function. Recent research highlights the significant role of gut microbiota in these interactions, with dysbiosis shown to correlate with central nervous system disorders such as autism, anxiety, and functional gastrointestinal issues. MATERIAL AND METHODS In this article review and analysis of the available literature was done. Literature was searched from Google Scholar, Pub med, Meds cape and narrative review was performed using keywords Gut-brain axis, enteric nervous system, and irritable bowel syndrome. This review seeks to underscore the key findings from studies on GBA, including its configuration, the microbiota involved, clinical associations, and advancements in therapy. RESULTS The gut microbiotas, which comprise trillion of microorganisms residing within the gastrointestinal tract, actively contribute to gut-brain communication by producing an array of metabolites, neurotransmitters, and immune modulators. Dysfunction within this axis has been implicated in a spectrum of disorders ranging from irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD) to depression, anxiety, and neurodegenerative conditions. CONCLUSION The present study reveals important insights into the neuro-physiological and neuro-psychological mechanism linked to various health issues and mental disorders, potentially leading to new targeted therapies.